Pengaruh Agama terhadap Konstitusi: Studi Komparasi Lembaga Konstitusi Negara Iran dan Indonesia - Fatni Erlina (Matan : Journal of Islam and Muslim Society, 2021)
This paper aims to find out the differences and similarities in the roles and positions of constitutional institutions between Iran and Indonesia. Several Islamic countries have succeeded in finding a harmonious form in elaborating between religion and democracy which is marked by the existence of a constitution. Conflicts between religion and democracy often occur in the preparation of the state administration sistem. Iran and Indonesia are both pioneers of the existence of a constitutional institution to ensure the enactment of the constitution as a basic agreement for all citizens and the government of a country. So it is important to know how the political commitment of a country in ensuring all power runs within constitutive boundaries. This research is a literature research, through normative juridical and socio-historical approaches, the data are then analyzed descriptively and comparatively. The results of the study show that the role and position of the constitutional institutions between Iran and Indonesia have a number of similarities and differences. This is due to the background of the cultural and religious patterns.